Carapanins A–C: new limonoids from andiroba (Carapa guianensis) fruit oil. Issue 45 (6th November 2020) - Kikuchi, Takashi; Akita, Keiko; Koike, Hiroki; In, Yasuko; Yamada, Takeshi; Tanaka, Reiko
Abstract : Carapanin A with a γ-lactone at C-15/C-30, and carapanin B with a C-16/C-30 δ-lactone ring were isolated from the fruit oil of Carapa guianensis together with carapanin C. Abstract : Carapanins A–C (1–3 ) were isolated from the fruit oil of Carapa guianensis . Compounds 1 and 2 are limonoids with unique structures. Namely, compound 1 is an andirobin-type limonoid with a C-15/C-30 γ-lactone instead of the δ-lactone of the D-ring, and compound 2 is a mexicanolide-type limonoid with a C-16/C-30 δ-lactone ring. The absolute structures of 1 and 2 were determined using X-ray crystallography, whereas the structure of 3 was established mainly via NMR and mass spectroscopy. The inhibitory effects of 1–3 on nitric oxide production were evaluated, and it was revealed that 2 and 3 were potent nitric oxide inhibitors.